Evaluating the effectiveness of a course taught to microbiology students: Usefulness of vocabulary, speaking activities, and materials - Chinambu, Mauli (2022)
This research paper analyzes the extent to which teaching vocabulary and speaking skills to a group of students of Microbiology from the University of Costa Rica can be effective at improving language skills. Therefore, both quantitative and qualitative method approaches were used to examine the data and the level of language competency the students required in order to become proficient in the language. The participants enrolled in an ESP course that covered real-life pre-tasks and main tasks to develop reading and speaking abilities. Additionally, after administering the pretest and post-test, results revealed that teaching the English for Microbiologists course had an impact on the participants’ language competency. The researchers discussed the outstanding results that were included in the findings of this paper to suggest the effectiveness of integrating tasks that were significant to accomplish the expected results. In conclusion, teaching vocabulary and speaking skills to microbiologists can improve the students’ proficiency in the English language. Learners need to enhance these skills as their academic and professional field demands a high level of comprehension and ability to interact with the plethora of English scientific articles.